1995
DOI: 10.1002/jctb.280630112
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid coatings for the prevention of membrane fouling

Abstract: The aim of the present work was the development of phosphorylcholine-based treatments for biofiltration membranes and the demonstration that such treatments prevent or inhibit protein fouling. Microfiltration membranes of cellulose triacetate, polyether sulphone and polyvinylidene fluoride were etched with oxygen in a plasma chamber to generate surface hydroxyl groups and were then treated with the monomer 2-methacryloyloxyethyl phosphorylcholine. These membranes were evaluated with water, buffer, bovine serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Early studies on material surface modifications were performed with single zwitterions, but macromolecular approaches have gained increasing importance mainly because polyzwitterions provide a more robust coating and are more efficient at blocking original surface ions (44, 45). This finding has received strong support by adsorption experiments of fibrinogen and cells such as fibroblasts or platelets on surfaces with different coverage of pSBE or pCB brushes, where the capability to prevent fouling correlated with the degree of grafting (4648).…”
Section: Polyzwitterions: Beyond Antifoulingmentioning
confidence: 99%
“…Early studies on material surface modifications were performed with single zwitterions, but macromolecular approaches have gained increasing importance mainly because polyzwitterions provide a more robust coating and are more efficient at blocking original surface ions (44, 45). This finding has received strong support by adsorption experiments of fibrinogen and cells such as fibroblasts or platelets on surfaces with different coverage of pSBE or pCB brushes, where the capability to prevent fouling correlated with the degree of grafting (4648).…”
Section: Polyzwitterions: Beyond Antifoulingmentioning
confidence: 99%
“…Over time the biomolecules within the body will react with the materials of the device, possibly leading to the passivation and reduced functionality of the device [68,69]. For example, the accumulation of proteins in the pores of the material around the drug output port eventually obstructs it [70]. To prevent biofouling, various types of coatings in addition to the device packaging are used.…”
Section: Biocompatibilitymentioning
confidence: 99%
“…The thickness of these fouling layers has been estimated to be in the range of 20 nm to 0.5 m. 29 In-vivo microdialysis, in-vitro cell, and protein fouling studies have confirmed that membrane biofouling results in decreased sensor signal strength. 30,31 5 m Figure 2. A scanning-electron micrograph of PEGylated, platinum-coated nanoporous alumina membrane after exposure to human platelet-rich plasma.…”
Section: In-vivo Applications: Challenges and Promising Solutionsmentioning
confidence: 99%